KETERGANTUNGAN MAHASISWA TERHADAP ROKOK - Hadinoto, Hadinoto; Suhesti, Eni; Ikhwan, Muhammad (Fakultas Kehutanan Universitas Lancang Kuning, 2016)
One of the sources of air pollutants are carried by most humans is cigarette smoke. Effects of smoking are numerous and dangerous to the health of both active smokers (actors) as well as passive smokers. The habit of smoking by the community of long standing. Smokers are generally carried out by people who are reaching adulthood from various circles, one of which is the student. Cigarette smoke is a pollutant for humans and the surrounding environment. Many diseases have been shown to arise from smoking, either directly or indirectly. This study aimed to: identify the level of dependence of Lancang Kuning University students Pekanbaru to smoking. This research was conducted at the campus of the University of Lancang Kuning. Data were obtained from filling the questionnaire will be processed in the following way Fargerstorm Tolerance Questionnaire Br J Addict. The number of respondents as many as 30 students obtained the degree of dependence on cigarettes ranging from mild, moderate and height / weight. Several factors are thought to affect, among other things such as limited money (still depending on shipment parent), time to smoke limited (for lectures and practicum) and there is an effort to save money. In this study, the students obtained the degree of dependence on cigarettes: lightweight (6.67%), moderate (70%) and high (23.33%).